The Modern Land-Grant University - Sternberg, Robert J. (Book collections on Project MUSE., 2014)
"In an increasingly competitive higher education environment, America's public universities are seeking ways to differentiate themselves. This book suggests that a hopeful vision of what a university should be lies in a reexamination of the "land-grant mission," the common system of values originally set forth in the Morrill Land Grant Acts of 1862 and 1890, which established a new system of practically oriented higher learning across the United States. While hard to define, these values are often expressed by the one hundred or so institutions that currently define themselves as "land grants" under the three pillars of research, teaching, and engagement/extension. In order to understand the unique character of a modern land-grant institution, this book focuses especially but not exclusively on the multiple components of a single organization, Oklahoma State University, founded in 1890 and currently enrolling 35,000 students across five campuses. Contributors from across the university focus on what the land-grant mission means to them in their daily endeavors, whether that be crafting the undergraduate academic experience, stimulating research, or engaging with the community through extension activities. The twenty contributions are divided into four parts, exploring in turn the core mission of the modern land-grant university, the university environment, the university's public value, and its accountability. The volume ends with an epilogue by the editor, which summarizes the values underlying the activities of land-grant institutions"--